Janus All‐Cis 2, 3, 4, 5, 6‐Pentafluorocyclohexyl Building Blocks Applied to Medicinal Chemistry and Bioactives Discovery Chemistry. Issue 64 (6th October 2021) - Clark, Joshua L.; Neyyappadath, Rifahath M.; Yu, Cihang; Slawin, Alexandra M. Z.; Cordes, David B.; O'Hagan, David
Abstract: Monoalkylated derivatives of the unusually polar all‐ cis 2, 3, 4, 5, 6‐ pentafluorocyclohexyl (Janus face) motif are prepared starting from an aryl hydrogenation of 2, 3, 4, 5, 6‐ pentafluorophenylacetate methyl ester 15 . The method used Zeng's Rh(CAAC) carbene catalyst 4 in the hydrogenation following the protocol developed by Glorius. The resultant Janus pentafluorocyclohexylacetate methyl ester 16 was converted to the corresponding alcohol 18, aldehyde 13, bromide 29 and azide 14 through functional group manipulations, and some of these building blocks were used in Ugi‐multicomponent and Cu‐catalysed click reactions. NBoc protected pentafluoroarylphenylalanine methyl ester 35 was also subject to an aryl hydrogenation, and then deprotection to generate the Janus face β‐pentafluorocyclohexyl‐alanine amino acid 15, which was incorporated into representative members of an emerging class of candidate antiviral compounds. Log P measurements demonstrate that the all‐ cis 2, 3, 4, 5, 6‐pentafluorocyclohexyl ring system is more polar than a phenyl ring. In overview the paper introduces new building blocks containing this Janus ring and demonstrates their progression to molecules typically used in bioactives discovery programmes. Abstract : Janus all‐ cis 2, 3, 4, 5, 6‐pentafluorocyclohexyl building blocks have been incorporated into medicinal chemistry type products. These cyclohexanes have polarized faces and represent a unique motif for medicinal chemistry. The paper introduces a range of new accessible building blocks which can be elaborated into a diversity of drug type structures demonstrating their wider utility for exploration in bioactives discovery chemistry.